Indigenous Wisdom of Ayurvedic Drugs to Treat Liver Disorders-Review Article: Life Sciences - Maheshwari, Devanshi; Rathi, Bharat; Rathi, Renu; Shinde, Aditi R. (International Journal of Life Science and Pharma Research, 2023)
The liver, a vital organ in the body, synthesizes hormones, decomposes RBC in the blood, and regulates glycogen storage. The liver also performs detoxification and is the primary site for drug metabolism. Therefore, hepatoprotective medications are necessary to keep the liver in good health. Ayurvedic drugs are widely used as hepatoprotective agents. The study aims to review the Yakrit (liver) concept in Ayurvedic literature, identify hepatoprotective plants from classical Ayurveda texts, and understand their mode of action on the liver based on existing scientific evidence. The classical Ayurveda literature and electronic databases such as Google Scholar, PubMed, Web of Science, and ARP were searched until October 2022 to find relevant studies using MESH terms. The search of classical Ayurveda texts showed several herbal sources that are advocated for use in liver disorders. The in vivo studies for these plants showed that seven protected the liver from CCl4-induced hepatic damage. Furthermore, the levels of liver enzymes were reduced, and there was evidence of reversal of fatty changes in the liver in mice fed with a high-fat diet. One of the essential organs that aid in sustaining bodily health is the liver. Some plants have been endowed by nature with the ability to treat, prevent, and cure liver disorders while causing fewer negative effects. Herb-based Ayurveda drugs can be a potent source of hepatoprotective agents, though detailed studies need to be conducted to generate more substantial evidence.